Memperingati Tahun Baru Cina sambil Melestarikan Warisan: Pengalaman Komunitas Cina di Yogyakarta - Rezza Maulana (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2015)
Since Abdurrahman Wahid had revoked the banning of publiccelebration of Chinese tradition and Megawati had made Chinese New Year (Imlek) as national holiday, Chinese communities in various big cities in Indonesia began celebrating Imlek ceremony and conducting numerousritual activities. In Yogyakarta, Chinese communities do not only pray in temple and have family gathering, but also organize a festival in five days consecutively. This festival is well-known as Yogyakarta Chinese Cultural Weeks or Pekan Budaya Tionghoa Yogyakarta (PBTY). Recently, this eventhas become a new public space which is strategic for conserving Indonesian Chinese cultural heritage, either tangible or intangible. This article tries to elaborate of what and how the Pekan Budaya Tionghoa Yogyakarta (PBTY)traditionally conducted.